Livestock Nature, Status, Breeding and feeding system in Balochistan. - Shafiq, Muhammad; Quddus , Abdul; Zaman, Monica Qamar (Al-Burz, 2009)
Balochistan is a largest province of Pakistan in terms of area and its scattered population mainly depends on livestock. It is the major share in the agriculture economy of Balochistan. Indigenous ecological situation also favors the livestock (majority sheep and goat) to flourish in the province. There are few rainfalls, which has made the cultivation very hard as compare to other provinces of Pakistan. Most of area of Balochistan comprises rangelands. Which are solidly rocky. There are some parts of Balochistan, where there are natural postures for the herders. These peculiar natures of land characteristics differentiate it from all Pakistan. Additionally, climate is most suitable for small ruminant to grow here at the hilly parts of the country. Hence, this paper is an attempt to highlight the nature, status, breeding and feeding system of Balochistan.